Physical and chemical characterization of spray-dried mango juice powder - Jamarolin, Abigail S.; Francisco, Ma. Leonora dL. (2002., 2002)
ABSTRACT Spray-dried mango juice powder was formulated and the effect of drying temperature and maltodextrin as bulking agent on the quality spray-dried mango juice powder was determined. Formulation and process development of the product include the use of 30% mango puree as starting material, 10% sodium caseinate and 2% tricalcium phosphate (TCP) as anti-caking agent and a feedrate of eight rpm using a fabricated spray-dryer. Spray drying temperature used were 120, 130 and 140°C and the level of maltodextrin varied from 10 to 30%. The effects on the physicochemical properties such as pH, titrable acidity and moisture content and color showed significant differences for all treatments across all samples tested with varying temperature and maltodextrin.Reconstitution preperties that were investigated include cloud stability, solubility index, dispersibility, flowability and sinkability tests. Statistical analysis revealed that the level of maltodextrin has a significant effect on these properties. On the other hand, temperature has no significant effect. A decreasing trend in cloud stability was observed as the percentage of maltodextrin increased. Mango juice powders that contain 30% maltodextrin exhibited a very high solubility index indicating lesser soluble powders. Dispersibility, flowability and sinkability tests were measured qualitatively. All samples with 30% maltodextrin showed many lumps upon dispersion.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fruit juices; Beverages